First, rewrite the expression as:
#(9/9^-1)(a/a^-2)(b^-3/b^5)#
Next, use these rules of exponents to divide the #9# and #a# terms:
#a = a^color(red)(1)# and #x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#
#(9/9^-1)(a/a^-2)(b^-3/b^5) => (9^color(red)(1)/9^color(blue)(-1))(a^color(red)(1)/a^color(blue)(-2))(b^-3/b^5) =>#
#9^(color(red)(1)-color(blue)(-1))a^(color(red)(1)-color(blue)(-2))(b^-3/b^5) => 9^(color(red)(1)+color(blue)(1))a^(color(red)(1)+color(blue)(2))(b^-3/b^5) =>#
#9^2a^3(b^-3/b^5) => 81a^3(b^-3/b^5)#
Now, use this rule of exponents to divide the #b# terms:
#x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))#
#81a^3(b^color(red)(-3)/b^color(blue)(5)) => 81a^3(1/b^(color(blue)(5)-color(red)(-3))) => 81a^3(1/b^(color(blue)(5)+color(red)(3))) =>#
#81a^3(1/b^8) =>#
#(81a^3)/b^8#